A systematic review on lecturing in contemporary university teaching - Tronchoni, Héctor; Izquierdo, Conrad; Anguera, M. Teresa (Frontiers in Psychology, 2022)
Introduction Articles published in scientific journals, concerning the present and future of the lecture format in university education in the twenty-first century are framed within organizational settings that drive teaching methodologies in line with educational policies. The following two research questions have arisen from articles in which debate the continuity of this teaching modality and propose improvements of a different nature: (1) Is there an interest in renovating the lecture format among the international research community whose remit is university teaching methods? and (2) What improvements to the lecture format do the reviewed articles suggest, within the framework of the communicative matrix of interactive learning? Method We have carried out a systematic review guided by the PRISMA approach, emphasizing the interest in methodological conceptual commitment, paying attention to documents published in journals with an impact factor. The search strategy was applied homogeneously in three databases: ERIC, PsycInfo, and Web of Science, following the systematic process of inclusion/exclusion. Results Forty-five articles were selected with a range of 0–78 quotations, from different fields of knowledge and five continents; 12 articles are from journals with a JCR impact factor. The journal articles cover communicative (21), cognitive (13) and active-practical perspectives (11); the predominant governing aim of the analyzed improvements is connected with the attendees’ academic performance results (24); the reviewed studies belong mainly to the quantitative paradigm (42). The considerations derived from the results (45) cover formative, technical and/or critical aspects. Discussion and conclusions Whilst positively valuing all these efforts promoted by the European Higher Education Area, we have also verified the lack of contributions in line with our concerns that embrace the need to develop an in-depth conceptualization, supported by a methodology that is sensitive to the complexity of the oral communication format between an expert actor and non-specialized actors who wish to connect and collaborate with the expert in the production of knowledge.